Composite hydrogel for resisting bacteria and repairing decayed teeth and preparation method of composite hydrogel
By crosslinking soluble starch, polyvinyl alcohol and L-arginine-loaded calcium carbonate nanoparticles with glucose oxidase, a composite hydrogel with good mechanical and antibacterial properties is solved, the complex hydrogel preparation process in the dental field is solved. and the problem of insufficient performance, low-cost, simple preparation and effective antibacterial and caries repair effects are achieved.
Patent Information
- Application Number
- CN202411359086.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
AI Technical Summary
In the application of existing hydrogels in the dental field, there are problems such as complex preparation process, high cost, insufficient biocompatibility and mechanical properties, and it is difficult to effectively be used for antibacterial and caries repair.
Compound hydrogels are formed by cross-linking soluble starch, polymer materials (such as polyvinyl alcohol, hyaluronic acid or collagen) with L-arginine-loaded calcium carbonate nanoparticles and glucose oxidase through crosslinking agents, and gas diffusion is used. CaCO3@L-Arg nanoparticles were prepared and cross-linked by sodium tetraborate decahydrate to form a composite hydrogel with good mechanical properties and antibacterial effects.
It realizes low-cost and simple preparation of composite hydrogels, has good mechanical properties, antibacterial effects and remineralized enamel ability, can quickly degrade and release hydrogen peroxide and nitric oxide under weak acid conditions, suitable for large-scale Promotion.
Smart Images

Figure CN119214994A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogel preparation, and relates to a composite hydrogel for antibacterial and caries repairing and a preparation method thereof. Background Art
[0002] Dental caries is a common dental disease with a very high incidence rate. About 2.3 billion people suffer from dental caries worldwide. The main cause of dental caries is that the dynamic balance of mineralization and demineralization in the enamel is broken, and a large amount of calcium ions and phosphate ions are lost. When dental caries lesions occur, bacteria (mainly Streptococcus mutans) attach to the enamel to form dental plaque, and produce a large amount of acidic substances through sugar metabolism, causing the pH of some areas on the surface of the enamel to drop significantly (below 5.5), prompting the dissolution of hydroxyapatite. If not treated in time, as the disease progresses, the lesions enter the dentin from the enamel, and the mineralized tissue is continuously destroyed and disintegrated, gradually forming caries. Microorganisms that reach the dentin can cause inflammatory reactions such as pulpitis and periodontitis. If not treated, it may cause permanent tissue loss, thereby reducing the ability of periodontal tissue to repair itself. Bacterial colonization in the root canal can lead to blood vessel and nerve death, and complications such as sepsis, cardiovascular disease, shock, and surrounding bone and tissue infection may occur. Because mature tooth enamel does not contain cells and has no regenerative ability, once damaged, it can only be repaired through external treatment, which is crucial for the prevention and treatment of caries. As the research and application of hydrogels gradually deepen, it has expanded to the field of dentistry.
[0003] As a kind of soft material with excellent physical and chemical properties and mechanical properties, hydrogel has a three-dimensional porous structure composed of hydrophilic polymers through covalent or non-covalent interactions, which gives it the ability to encapsulate and transport drugs in a directional manner, and generally has good biocompatibility. Since the covalent or non-covalent interaction of the gel is easily affected by external factors, a variety of environmentally responsive hydrogels have been developed. For example, pH responsiveness, temperature responsiveness, biomolecule responsiveness, force responsiveness, and ROS responsiveness. Environmentally responsive hydrogels have been widely studied in the field of drug sustained release. According to the matrix material, hydrogels can be divided into three categories: natural polymers, synthetic polymers, and natural-synthetic hydrogels. For example, natural polymer hydrogels are prepared using natural materials such as hyaluronic acid, chitosan, alginate, starch, etc. as matrix materials, while synthetic polymer hydrogels are prepared using synthetic materials such as polyethylene glycol, polyvinyl alcohol, and polyacrylic acid. Natural polymer hydrogels generally have the advantages of low cytotoxicity, excellent biocompatibility, biodegradability, and low price, but are slightly lacking in mechanical properties; while synthetic polymer hydrogels generally have excellent mechanical strength, but lack biocompatibility and degradability. How to combine the advantages of the two, that is, to obtain natural-synthetic hydrogels with excellent mechanical and biocompatibility, is a key issue that needs to be solved.
[0004] Starch is a natural polysaccharide that is usually derived from plants and is therefore friendly to the human body and the environment. It does not contain harmful chemicals, does not cause allergic or toxic reactions, has good biocompatibility, and is suitable for the medical field. As a degradable material, starch has good water absorption and water retention properties, can form a stable hydrogel structure, and can be quickly decomposed into harmless products under certain conditions. Starch is a widely available resource and relatively cheap, so it is cost-effective in large-scale production. This makes starch hydrogels more competitive in many application areas. Polyvinyl alcohol (PVA) is a water-soluble polymer. Its molecular chain contains a large number of hydroxyl groups, so it has good water solubility and is easy to form a cross-linked network with starch through hydrogen bonds. In addition, the ultra-high polymerization of PVA helps to improve the mechanical strength of the hydrogel by increasing the intramolecular cross-linking degree and the degree of entanglement of the network. Starch and PVA hydrogels have been widely used in the biological field as matrix materials.
[0005] Using hydrogel as a carrier to load antimicrobial drugs is still one of the mainstream strategies. However, after repeated exposure to antimicrobial drugs, bacteria undergo corresponding changes in their structure, physiology, and biochemical functions, which can easily form drug-resistant mutant strains. Antimicrobial substances mainly include antibiotics (ciprofloxacin, gentamicin, vancomycin and cephalosporin), biological extracts (curcumin, ephedrine, tannic acid), etc. Cascade antibacterial is an emerging antibacterial method that can be achieved by using hydrogen peroxide (H2O2) to oxidize the guanidine group of arginine to produce nitric oxide (NO). Nitric oxide is a key molecule produced endogenously with low cytotoxicity. It is known to be associated with a variety of important biological processes, such as apoptosis, angiogenesis, neurotransmission, platelet aggregation and adhesion, immune response, etc. In addition, as a broad-spectrum antibiotic, NO can easily pass through biofilms and convert into nitrogen trioxide (N2O3) and peroxynitrite (ONOO - ) to achieve bacterial lipid peroxidation, cell membrane rupture and DNA deamination. Compared with traditional antibiotics, bacteria are less likely to develop resistance to H2O2 and NO.
[0006] Although hydrogel can be used as an excellent carrier to treat dental diseases, its preparation process is often very complicated and its practical value is low. Therefore, we should find a simple, efficient and low-cost preparation method to prepare composite hydrogels for antibacterial and caries repair to improve the practical value of hydrogels. Summary of the invention
[0007] In view of this, one of the objects of the present invention is to provide a composite hydrogel for antibacterial and caries repair; the second object of the present invention is to provide a method for preparing the composite hydrogel for antibacterial and caries repair.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] 1. A composite hydrogel for antibacterial and caries repair, wherein the composite hydrogel is formed by cross-linking soluble starch, polymer materials, calcium carbonate nanoparticles loaded with L-arginine (CaCO3@L-Arg nanoparticles) and glucose oxidase (GOx) through a cross-linking agent;
[0010] The polymer material is any one of polyvinyl alcohol (PVA), polyethylene glycol (PEG), hyaluronic acid or collagen;
[0011] The cross-linking agent is sodium tetraborate decahydrate or boric acid.
[0012] Preferably, the L-arginine-loaded calcium carbonate nanoparticles (CaCO3@L-Arg nanoparticles) are prepared from CaCl2 and L-arginine (L-Arg) by a gas diffusion method, and the specific preparation method is as follows:
[0013] A triple-distilled aqueous solution of L-arginine (L-Arg) is added to an anhydrous ethanol solution of CaCl2, and the mixture is sealed with a double-layer tin foil with holes, and the mixture is transferred to a gas reactor. Several vials containing NH4HCO3 and sealed with tin foil with holes are also placed at the bottom of the gas reactor. The bottom of the gas reactor is placed in an oven, reacted at 30°C for 24 to 36 hours, and then centrifuged. After repeated washing, calcium carbonate nanoparticles loaded with L-arginine (CaCO3@L-Arg nanoparticles) are obtained.
[0014] Further preferably, the mass ratio of CaCl2 in the anhydrous ethanol solution of CaCl2 to L-arginine (L-Arg) in the triple-distilled aqueous solution of L-arginine (L-Arg) is 2:1.
[0015] Further preferably, the solvent used in the washing process is anhydrous ethanol.
[0016] Preferably, the mass ratio of the soluble starch, the polymer material, the L-arginine-loaded calcium carbonate nanoparticles (CaCO3@L-Arg nanoparticles), the glucose oxidase (GOx) and the cross-linking agent is 1000:300-500:50:4:18.3-27.4.
[0017] 2. A method for preparing the composite hydrogel, comprising the following steps:
[0018] Soluble starch and polymer materials are dissolved in PBS buffer solution, heated and stirred in an oil bath to dissolve them, then the oil bath is removed and stirring is continued until the temperature drops to room temperature. L-arginine-loaded calcium carbonate nanoparticles (CaCO3@L-Arg nanoparticles) and glucose oxidase (GOx) are added, stirred and ultrasonically mixed until evenly mixed, then a PBS solution containing a cross-linking agent is added, and stirring is continued to obtain a composite hydrogel for antibacterial and caries repair.
[0019] Preferably, the temperature of heating and stirring in the oil bath is 85-95° C. and the time is 1-2 h.
[0020] The beneficial effects of the present invention are as follows: the present invention discloses a composite hydrogel for antibacterial and dental caries repair, wherein the composite hydrogel matrix material is composed of soluble starch and polymer material, PBS as solvent, loaded CaCO3@L-Arg nanoparticles and glucose oxidase (GOx) cross-linked by a cross-linking agent. The composite hydrogel of the present invention has the following advantages: (1) it has good mechanical and adhesive properties and can be arbitrarily shaped; (2) it can accelerate degradation under weakly acidic conditions and release hydrogen peroxide and nitric oxide; (3) it has good antibacterial and anti-biofilm effects; (4) it has the ability to remineralize tooth enamel; (5) the raw materials used in the preparation process are low in cost, the preparation process is simple, and it is suitable for large-scale promotion. The composite hydrogel of the present invention is gelled by a simple method with low raw material cost, and it is adhered to the dental caries during use, and its own pH and glucose sensitivity and salivary amylase present in the oral cavity can be used to achieve rapid degradation between meals. The salivary amylase and loaded glucose oxidase mediate the enzyme cascade reaction to produce hydrogen peroxide and nitric oxide to achieve the effect of anti-dental caries biofilm. At the same time, the demineralized tooth enamel is repaired. Therefore, the composite hydrogel for antibacterial and caries repair of the present invention has a good application prospect.
[0021] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0023] Figure 1 Transmission electron microscopy (a) and mapping image (b) of CaCO3@L-Arg nanoparticles prepared in Example 1;
[0024] Figure 2is a particle size diagram of the CaCO3@L-Arg nanoparticles prepared in Example 1;
[0025] Figure 3 is the XPS spectrum of the CaCO3@L-Arg nanoparticles prepared in Example 1;
[0026] Figure 4 This is a scanning electron micrograph of the composite hydrogel for antibacterial and caries repair prepared in Example 1;
[0027] Figure 5 Mapping image of composite hydrogel for antibacterial and caries repair;
[0028] Figure 6 is the infrared spectrum of the composite hydrogel for antibacterial and caries repair prepared in Example 1;
[0029] Figure 7 The tensile properties of the composite hydrogel for antibacterial and caries repair prepared in Example 1;
[0030] Figure 8 The adhesion performance of the composite hydrogel for antibacterial and caries repair prepared in Example 1 on the hydroxyapatite sheet;
[0031] Fig. 9 The adhesion and arbitrary plasticity of the composite hydrogel for antibacterial and caries repair prepared in Example 1 to teeth;
[0032] Fig.10 The degradation capacity of the composite hydrogel for antibacterial and caries repair prepared in Example 1 at initial pH=5 and pH=7;
[0033] Fig.11 The hydrogen peroxide release capacity of the composite hydrogel for antibacterial and caries repair prepared in Example 1 at initial pH=5 and pH=7;
[0034] Fig.12 The nitric oxide release capacity of the composite hydrogel for antibacterial and caries repair prepared in Example 1 at initial pH=5 and pH=7;
[0035] Fig.13The antibacterial abilities of different materials against Streptococcus mutans (S. mutans), Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) at initial pH = 5, wherein Control, Gel++CaCO3@L-Arg, Gel+GOx, and Gel+GOx+CaCO3@L-Arg are the control group, the composite hydrogel loaded with CaCO3@L-Arg nanoparticles, the composite hydrogel loaded with GOx, and the composite hydrogel loaded with GOx and CaCO3@L-Arg nanoparticles, respectively;
[0036] Fig.14 is the ability of different materials to resist biofilm of Streptococcus mutans at initial pH=5, where Control, Gel+GOx, and Gel+GOx+CaCO3@L-Arg are the control group, composite hydrogel loaded with GOx, and composite hydrogel loaded with GOx and CaCO3@L-Arg nanoparticles, respectively;
[0037] Fig.15 This is a surface scanning electron micrograph of the composite hydrogel for antibacterial and caries repair prepared in Example 1 after treating the enamel after acid etching for nine times, wherein a is the junction between the mineralized area and the acid-etched area, and b is the mineralized area;
[0038] Fig.16 This is a cross-sectional scanning electron micrograph of the composite hydrogel for antibacterial and caries repair prepared in Example 1 after treating the enamel after acid etching for nine times;
[0039] Fig.17 The hardness change of the enamel surface before and after acid etching treated with the composite hydrogel for antibacterial and caries repair prepared in Example 1. DETAILED DESCRIPTION
[0040] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.
[0041] Example 1
[0042] A composite hydrogel for antibacterial and caries repair, the specific preparation method is as follows:
[0043] (1) Preparation of CaCO3@L-Arg nanoparticles by gas diffusion method: a. Add L-arginine (L-Arg) in a three-distilled water solution (dissolve 75 mg of L-Arg in 500 μL of three-distilled water) to an anhydrous ethanol solution of CaCl2 (add 150 mg of anhydrous CaCl2 to 100 ml of anhydrous ethanol and dissolve it completely by ultrasound). After mixing, transfer the mixture to a glass bottle, seal the bottle with a double-layer tin foil with two holes, and then transfer the glass bottle to a gas reactor; b. Divide 80 g of NH4HCO3 into 4 small bottles, seal the bottles with tin foil with four small holes, and then place the small bottles at the bottom of the above-mentioned gas reactor; c. Place the above-mentioned gas reactor in an oven and react at 30°C for 36 hours. After the reaction is completed, centrifuge the product and wash it three times with anhydrous ethanol to obtain CaCO3@L-Arg nanoparticles, which are stored in anhydrous ethanol.
[0044] (2) Preparation of composite hydrogel for antibacterial and caries repair: a. Add 1 g soluble starch and 0.3 g PVA1799 to 8 mL PBS buffer solution, stir in a 90°C oil bath for 1 h to completely dissolve the starch and PVA1799, transfer to a beaker, and continue stirring until the solution cools to room temperature; b. Continue to add 50 mg of the CaCO3@L-Arg nanoparticles prepared in the above step (1) and 4 mg of glucose oxidase (GOx) to the beaker, stir ultrasonically for 30 min, and then quickly add 4 ml of 12 mmol / L sodium tetraborate decahydrate PBS solution under continuous stirring to obtain a composite hydrogel for antibacterial and caries repair, which can be stored at 4°C.
[0045] Example 2
[0046] A composite hydrogel for antibacterial and caries repair, the specific preparation method is as follows:
[0047] (1) Preparation of CaCO3@L-Arg nanoparticles by gas diffusion method: a. Add L-arginine (L-Arg) in a three-distilled water solution (dissolve 75 mg of L-Arg in 500 μL of three-distilled water) to an anhydrous ethanol solution of CaCl2 (add 150 mg of anhydrous CaCl2 to 100 ml of anhydrous ethanol and dissolve it completely by ultrasound). After mixing, transfer the mixture to a glass bottle, seal the bottle with a double-layer tin foil with two holes, and then transfer the glass bottle to a gas reactor; b. Divide 80 g of NH4HCO3 into 4 small bottles, seal the bottles with tin foil with four small holes, and then place the small bottles at the bottom of the above-mentioned gas reactor; c. Place the above-mentioned gas reactor in an oven and react at 30°C for 24 hours. After the reaction is completed, centrifuge the product and wash it three times with anhydrous ethanol to obtain CaCO3@L-Arg nanoparticles, which are stored in anhydrous ethanol.
[0048] (2) Preparation of composite hydrogel for antibacterial and caries repair: a. Add 1 g soluble starch and 0.4 g PVA1799 to 8 mL PBS buffer solution, stir in an 85°C oil bath for 1.5 h to completely dissolve the starch and PVA1799, transfer to a beaker, and continue stirring until the solution cools to room temperature; b. Continue to add 50 mg of the CaCO3@L-Arg nanoparticles prepared in the above step (1) and 4 mg of glucose oxidase (GOx) to the beaker, stir ultrasonically for 30 min, and then quickly add 4 ml of 12 mmol / L sodium tetraborate decahydrate PBS solution under continuous stirring to obtain a composite hydrogel for antibacterial and caries repair, which can be stored at 4°C.
[0049] Example 3
[0050] A composite hydrogel for antibacterial and caries repair, the specific preparation method is as follows:
[0051] (1) Preparation of CaCO3@L-Arg nanoparticles by gas diffusion method: a. Add L-arginine (L-Arg) in a three-distilled water solution (dissolve 75 mg of L-Arg in 500 μL of three-distilled water) to an anhydrous ethanol solution of CaCl2 (add 150 mg of anhydrous CaCl2 to 100 ml of anhydrous ethanol and dissolve it completely by ultrasound). After mixing, transfer the mixture to a glass bottle, seal the bottle with a double-layer tin foil with two holes, and then transfer the glass bottle to a gas reactor; b. Divide 80 g of NH4HCO3 into 4 small bottles, seal the bottles with tin foil with four small holes, and then place the small bottles at the bottom of the above-mentioned gas reactor; c. Place the above-mentioned gas reactor in an oven and react at 30°C for 24 hours. After the reaction is completed, centrifuge the product and wash it three times with anhydrous ethanol to obtain CaCO3@L-Arg nanoparticles, which are stored in anhydrous ethanol.
[0052] (2) Preparation of composite hydrogel for antibacterial and caries repair: a. Add 1 g soluble starch and 0.5 g PVA 1799 into 8 mL PBS buffer solution, stir in an 85°C oil bath for 2 h to completely dissolve the starch and PVA1799, transfer to a beaker, and continue stirring until the solution cools to room temperature; b. Continue to add 50 mg of the CaCO3@L-Arg nanoparticles prepared in the above step (1) and 4 mg of glucose oxidase (GOx) into the beaker, stir ultrasonically for 30 min, and then quickly add 4 ml of 12 mmol / L sodium tetraborate decahydrate PBS solution under continuous stirring to obtain a composite hydrogel for antibacterial and caries repair, which can be stored at 4°C.
[0053] Example 4
[0054] A composite hydrogel for antibacterial and caries repair, the specific preparation method is as follows:
[0055] (1) Preparation of CaCO3@L-Arg nanoparticles by gas diffusion method: a. Add L-arginine (L-Arg) in a three-distilled water solution (dissolve 75 mg of L-Arg in 500 μL of three-distilled water) to an anhydrous ethanol solution of CaCl2 (add 150 mg of anhydrous CaCl2 to 100 ml of anhydrous ethanol and dissolve it completely by ultrasound). After mixing, transfer the mixture to a glass bottle, seal the bottle with a double-layer tin foil with two holes, and then transfer the glass bottle to a gas reactor; b. Divide 80 g of NH4HCO3 into 4 small bottles, seal the bottles with tin foil with four small holes, and then place the small bottles at the bottom of the above-mentioned gas reactor; c. Place the above-mentioned gas reactor in an oven and react at 30°C for 36 hours. After the reaction is completed, centrifuge the product and wash it three times with anhydrous ethanol to obtain CaCO3@L-Arg nanoparticles, which are stored in anhydrous ethanol.
[0056] (2) Preparation of composite hydrogel for antibacterial and caries repair: a. Add 1 g of soluble starch and 0.3 g of polyethylene glycol (PEG) to 8 mL of PBS buffer solution, stir in a 90°C oil bath for 1 h to completely dissolve the starch and PEG, transfer to a beaker, and continue stirring until the solution cools to room temperature; b. Continue to add 50 mg of the CaCO3@L-Arg nanoparticles prepared in the above step (1) and 4 mg of glucose oxidase (GOx) to the beaker, stir ultrasonically for 30 min, and then quickly add 4 ml of 12 mmol / L boric acid in PBS solution under continuous stirring to obtain a composite hydrogel for antibacterial and caries repair, which can be stored at 4°C.
[0057] Example 5
[0058] A composite hydrogel for antibacterial and caries repair, the specific preparation method is as follows:
[0059] (1) Preparation of CaCO3@L-Arg nanoparticles by gas diffusion method: a. Add L-arginine (L-Arg) in a three-distilled water solution (dissolve 75 mg of L-Arg in 500 μL of three-distilled water) to an anhydrous ethanol solution of CaCl2 (add 150 mg of anhydrous CaCl2 to 100 ml of anhydrous ethanol and dissolve it completely by ultrasound). After mixing, transfer the mixture to a glass bottle, seal the bottle with a double-layer tin foil with two holes, and then transfer the glass bottle to a gas reactor; b. Divide 80 g of NH4HCO3 into 4 small bottles, seal the bottles with tin foil with four small holes, and then place the small bottles at the bottom of the above-mentioned gas reactor; c. Place the above-mentioned gas reactor in an oven and react at 30°C for 36 hours. After the reaction is completed, centrifuge the product and wash it three times with anhydrous ethanol to obtain CaCO3@L-Arg nanoparticles, which are stored in anhydrous ethanol.
[0060] (2) Preparation of composite hydrogel for antibacterial and caries repair: a. Add 1 g soluble starch and 0.3 g hyaluronic acid to 8 mL PBS buffer solution, stir in a 90°C oil bath for 1.5 h to completely dissolve the starch and hyaluronic acid, transfer to a beaker, and continue stirring until the solution cools to room temperature; b. Continue to add 50 mg of the CaCO3@L-Arg nanoparticles prepared in the above step (1) and 4 mg of glucose oxidase (GOx) to the beaker, stir ultrasonically for 30 min, and then quickly add 4 ml of 18 mmol / L boric acid in PBS solution under continuous stirring to obtain a composite hydrogel for antibacterial and caries repair, which can be stored at 4°C.
[0061] Example 6
[0062] A composite hydrogel for antibacterial and caries repair, the specific preparation method is as follows:
[0063] (1) Preparation of CaCO3@L-Arg nanoparticles by gas diffusion method: a. Add L-arginine (L-Arg) in a three-distilled water solution (dissolve 75 mg of L-Arg in 500 μL of three-distilled water) to an anhydrous ethanol solution of CaCl2 (add 150 mg of anhydrous CaCl2 to 100 ml of anhydrous ethanol and dissolve it completely by ultrasound). After mixing, transfer the mixture to a glass bottle, seal the bottle with a double-layer tin foil with two holes, and then transfer the glass bottle to a gas reactor; b. Divide 80 g of NH4HCO3 into 4 small bottles, seal the bottles with tin foil with four small holes, and then place the small bottles at the bottom of the above-mentioned gas reactor; c. Place the above-mentioned gas reactor in an oven and react at 30°C for 36 hours. After the reaction is completed, centrifuge the product and wash it three times with anhydrous ethanol to obtain CaCO3@L-Arg nanoparticles, which are stored in anhydrous ethanol.
[0064] (2) Preparation of composite hydrogel for antibacterial and caries repair: a. Add 1 g soluble starch and 0.3 g collagen to 8 mL PBS buffer solution, stir in a 90°C oil bath for 1 h to completely dissolve the starch and collagen, transfer to a beaker, and continue stirring until the solution cools to room temperature; b. Continue to add 50 mg of the CaCO3@L-Arg nanoparticles prepared in the above step (1) and 4 mg of glucose oxidase (GOx) to the beaker, stir ultrasonically for 30 min, and then quickly add 4 ml of 18 mmol / L boric acid in PBS solution under continuous stirring to obtain a composite hydrogel for antibacterial and caries repair, which can be stored at 4°C.
[0065] Performance Testing
[0066] Figure 1The transmission electron microscope (a) and mapping image (b) of the CaCO3@L-Arg nanoparticles prepared in Example 1. Figure 1 It can be seen that the CaCO3@L-Arg nanoparticles prepared in Example 1 are spherical and successfully loaded with L-arginine. It can be seen that the preparation method obtained in step (1) of Example 1 can indeed prepare CaCO3@L-Arg nanoparticles.
[0067] Figure 2 The particle size diagram of CaCO3@L-Arg nanoparticles prepared in Example 1. Figure 2 It can be seen that the particle size of the CaCO3@L-Arg nanoparticles prepared in Example 1 is concentrated around 71 nm.
[0068] Figure 3 The XPS spectrum of CaCO3@L-Arg nanoparticles prepared in Example 1. Figure 3 It can be seen that the CaCO3@L-Arg nanoparticles prepared in Example 1 were indeed successfully loaded with L-arginine.
[0069] Figure 4 This is a scanning electron microscope image of the composite hydrogel for antibacterial and caries repair prepared in Example 1. Figure 4 It can be seen that the composite hydrogel prepared in Example 1 has a uniform pore structure.
[0070] Figure 5 This is a mapping image of the composite hydrogel for antibacterial and caries repair prepared in Example 1. Figure 5 It can be seen that CaCO3@L-Arg nanoparticles and GOx are uniformly dispersed in the composite hydrogel.
[0071] Figure 6 IR spectrum of the composite hydrogel for antibacterial and caries repair prepared in Example 1. Figure 6 It can be seen that the composite hydrogel for antibacterial and caries repair prepared in Example 1 has characteristic peaks of hydrogen phosphate and BO.
[0072] Figure 7 is the tensile property of the composite hydrogel for antibacterial and caries repair prepared in Example 1. Figure 7 It can be seen that the composite hydrogel for antibacterial and caries repair prepared in Example 1 has good tensile properties and can be stretched to 800% strain.
[0073] Figure 8 The adhesion performance of the composite hydrogel for antibacterial and caries repair prepared in Example 1 on the hydroxyapatite sheet. Figure 8It can be seen that the maximum adhesion strength of the composite hydrogel for antibacterial and caries repair prepared in Example 1 to the hydroxyapatite sheet is about 4.5 KPa.
[0074] Fig. 9 The adhesion and arbitrary plasticity of the composite hydrogel for antibacterial and caries repair prepared in Example 1 to teeth. Fig. 9 It can be seen that the composite hydrogel for antibacterial and caries repair prepared in Example 1 can adhere well to the tooth surface and can be arbitrarily shaped to fill caries cavities of different shapes.
[0075] Fig.10 The degradation capacity of the composite hydrogel for antibacterial and caries repair prepared in Example 1 at initial pH = 5 and pH = 7. Fig.10 It can be seen that due to the pH sensitivity of the borate bond, the degradation of the composite hydrogel for antibacterial and caries repair prepared in Example 1 was accelerated at initial pH=5 and pH=7.
[0076] Fig.11 The hydrogen peroxide release capacity of the composite hydrogel for antibacterial and caries repair prepared in Example 1 at initial pH = 5 and pH = 7. Fig.11 It can be seen that there is no significant difference in the concentration of hydrogen peroxide released by the composite hydrogel for antibacterial and caries repair prepared in Example 1 at initial pH=5 and pH=7.
[0077] Fig.12 The nitric oxide release capacity of the composite hydrogel for antibacterial and caries repair prepared in Example 1 at initial pH = 5 and pH = 7. Fig.12 It can be seen that since the CaCO3@L-Arg nanoparticles decomposed in large quantities under acidic conditions, thereby releasing more L-Arg, the release of nitric oxide from the composite hydrogel for antibacterial and caries repair prepared in Example 1 at an initial pH = 5 was about three times that at pH = 7.4.
[0078] Fig.13 The antibacterial ability of different materials against Streptococcus mutans (S. mutans), Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) at initial pH = 5, where Control, Gel++CaCO3@L-Arg, Gel+GOx, and Gel+GOx+CaCO3@L-Arg are the control group, composite hydrogel loaded with CaCO3@L-Arg nanoparticles, composite hydrogel loaded with GOx, and composite hydrogel loaded with GOx and CaCO3@L-Arg nanoparticles, respectively. Fig.13It can be seen that the composite hydrogel loaded with CaCO3@L-Arg nanoparticles has no antibacterial ability. The antibacterial rate of the composite hydrogel loaded with GOx against three bacteria is more than 74%, and the antibacterial rate of the composite hydrogel loaded with GOx and CaCO3@L-Arg nanoparticles is more than 98%. It can be seen that the composite hydrogel has excellent antibacterial properties.
[0079] Fig.14 The anti-strain biofilm ability of different materials at initial pH = 5, where Control, Gel + GOx, and Gel + GOx + CaCO3@L-Arg are the control group, the composite hydrogel loaded with GOx, and the composite hydrogel loaded with GOx and CaCO3@L-Arg nanoparticles, respectively. Fig.14 It can be seen that the antibacterial rate of the composite hydrogel loaded with GOx against Streptococcus mutans biofilm is about 63%, and the antibacterial rate of the composite hydrogel loaded with GOx and CaCO3@L-Arg nanoparticles is about 89%.
[0080] Fig.15 This is a surface scanning electron micrograph of the composite hydrogel for antibacterial and caries repair prepared in Example 1 after treating the enamel after acid etching for nine times, where a is the junction of the mineralized area and the acid-etched area, and b is the mineralized area. Fig.15 It can be seen that after the enamel after acid etching was treated nine times with the composite hydrogel for antibacterial and caries repair prepared in Example 1, there was an obvious boundary line between the mineralized area and the acid-etched area, the fish scale structure of the enamel in the acid-etched area was obvious, and the fish scale structure was almost invisible in the mineralized area, which was similar to before acid etching.
[0081] Fig.16 This is a cross-sectional scanning electron micrograph of the composite hydrogel for antibacterial and caries repair prepared in Example 1 after treating the enamel after acid etching for nine times. Fig.16 It can be seen that the composite hydrogel for antibacterial and caries repair prepared in Example 1 showed an obvious mineralized layer after acid etching for nine times of tooth enamel treatment.
[0082] Fig.17 The hardness change of the enamel surface before and after acid etching by the composite hydrogel for antibacterial and caries repair prepared in Example 1. Fig.17 It can be seen that the surface hardness of natural tooth enamel is about 322.06 HV, and the hardness drops sharply to about 149.94 HV after acid etching. The hardness is increased to 225.09 HV after three treatments with the composite hydrogel for antibacterial and caries repair prepared in Example 1, and to 277.33 HV after six treatments, and to 309.9 HV after nine treatments. It can be seen that the composite hydrogel for antibacterial and caries repair prepared in Example 1 can indeed improve the surface hardness of tooth enamel after treating it.
[0083] The above performance tests were also performed on the composite hydrogels for antibacterial and caries repair prepared in Example 2, Example 3, Example 4, Example 5, and Example 6. The results were similar to those of the composite hydrogels for antibacterial and caries repair in Example 1, and all had good adhesion, fast degradation rate, good antibacterial and anti-biofilm effects, remineralization ability of enamel, and low cost.
[0084] In summary, the present invention discloses a composite hydrogel for antibacterial and caries repair, wherein the composite hydrogel is formed by crosslinking soluble starch, polyvinyl alcohol (PVA), CaCO3-loaded L-Arg nanoparticles (CaCO3@L-Arg nanoparticles) and glucose oxidase (GOx) through sodium tetraborate decahydrate. The composite hydrogel of the present invention has the following advantages: (1) it has good mechanical and adhesive properties and can be arbitrarily shaped; (2) it can accelerate degradation under weakly acidic conditions and release hydrogen peroxide and nitric oxide; (3) it has good antibacterial and anti-biofilm effects; (4) it has the ability to remineralize tooth enamel; (5) the raw materials used in the preparation process are low in cost, the preparation process is simple, and it is suitable for large-scale promotion. The composite hydrogel of the present invention is gelled by a simple method with low raw material cost. During use, it is adhered to the caries, and its own pH and glucose sensitivity and the salivary amylase present in the oral cavity can be used to achieve rapid degradation between meals. The salivary amylase and the loaded glucose oxidase mediate the enzyme cascade reaction to produce hydrogen peroxide and nitric oxide to achieve the effect of anti-caries biofilm. At the same time, the demineralized enamel is repaired. Therefore, the composite hydrogel for antibacterial and caries repair of the present invention has a good application prospect.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A composite hydrogel for antibacterial and caries repair, characterized in that: The composite hydrogel is formed by cross-linking soluble starch, polymer materials, L-arginine-loaded calcium carbonate nanoparticles and glucose oxidase through a cross-linking agent; The polymer material is any one of polyvinyl alcohol, polyethylene glycol, hyaluronic acid or collagen; The cross-linking agent is sodium tetraborate decahydrate or boric acid.
2. The composite hydrogel according to claim 1, characterized in that The L-arginine-loaded calcium carbonate nanoparticles are prepared from CaCl2 and L-arginine by a gas diffusion method, and the specific preparation method is as follows: A triple-distilled aqueous solution of L-arginine is added to an anhydrous ethanol solution of CaCl2, and the mixture is sealed with a double-layer tin foil with holes, and the mixture is transferred to a gas reactor. Several vials containing NH4HCO3 and sealed with tin foil with holes are also placed at the bottom of the gas reactor. The bottom of the gas reactor is placed in an oven, reacted at 30°C for 24 to 36 hours, and then centrifuged. After repeated washing, calcium carbonate nanoparticles loaded with L-arginine are obtained.
3. The composite hydrogel according to claim 2, characterized in that The mass ratio of CaCl2 in the anhydrous ethanol solution of CaCl2 to L-arginine in the triple-distilled aqueous solution of L-arginine is 2:
1.
4. The composite hydrogel according to claim 2, characterized in that The solvent used in the washing process is anhydrous ethanol.
5. The composite hydrogel according to claim 1, characterized in that The mass ratio of the soluble starch, the polymer material, the calcium carbonate nanoparticles loaded with L-arginine, the glucose oxidase and the cross-linking agent is 1000:300-500:50:4:18.3-27.
4.
6. The method for preparing the composite hydrogel according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Soluble starch and polymer materials are dissolved in PBS buffer solution, heated and stirred in an oil bath to dissolve them, then the oil bath is removed and stirring is continued until the temperature drops to room temperature. L-arginine-loaded calcium carbonate nanoparticles and glucose oxidase are added, and after stirring and ultrasonic mixing to mix evenly, a PBS solution containing a cross-linking agent is added and stirring is continued to obtain a composite hydrogel for antibacterial and caries repair.
7. The preparation method according to claim 6, characterized in that: The heating and stirring in the oil bath is performed at a temperature of 85 to 95° C. and a time of 1 to 2 hours.
